Croatia: Demographic Policy and Family Law Combatting Demographic Decline - Korać Graovac, Aleksandra (Demographic Challenges in Central Europe: Legal and Family Policy Response, 2024)
This chapter focuses on family policy in Croatia, reviewing demographic data, the institutional framework for family policy, family support benefits (including the country’s generous maternity and paternity leave), child allowances, and baby bonus for the third and fourth child. The chapter explains state allowances and local (self-government) supported family allowances. Generational policy, tax and contribution benefits, family and work allowances, family-friendly provisions in the pension system (an additional 6-month period for each child), and the social security institutions supporting families are also reviewed within the family policy framework. In addition, the chapter discusses the advantages and disadvantages of the real estate tax for housing in areas of special state concern and the subsidisation of housing loans for families. Criticism of the fact that expenditures for social policy in Croatia are among the lowest in the European Union is also presented. Though it does not significantly or directly influence demography, family law is extremely important owing to the system of principles and the values that these principles reflect. In the context of family policy, this chapter describes the principles of family law, family law regulation concerning property rights between family members (the concept of the family home, rules for the division of family property, representation of the child in property matters, etc.). It also introduces the legal norms that regulate establishing the origin of the child, as well as the rights and duties related to maintenance among relatives that offer financial security to family members based on the principle of family solidarity. Given that every 20th child in Croatia is born through medically assisted reproduction, this procedure influences the fertility rate to some extent. Consequently, the Croatian state provides generous support for reproductive health. Keywords: Family policy, family allowance, child allowance, matrimonial property, family law, medically assisted reproduction, assisted reproductive technology